The Investigation of Hippocampus-Dependent Cognitive Decline Induced by Anesthesia/Surgery in Mice Through Integrated Behavioral Z-Scoring - Meng, Bo; Li, Xiaoyu; Lu, Bo; Liu, Rongjun; Yuan, Hui; Zhai, Xiaojie; Qin, Jinling; Chen, Zhang; Zheng, Jinwei; Chen, Junping (Frontiers in Behavioral Neuroscience, 2020)
Objective: Patients undergoing major surgeries may experience certain cognitive decline, which is known as postoperative delirium (POD) or postoperative cognitive dysfunction (POCD). We employed integrated behavioral Z-scoring introduced by Guilloux et al. to investigate the effects of fracture fixation under anesthesia on hippocampus-dependent memory in mice. Methods: ICR mice (12-14 months) underwent stabilized tibial fracture operation under sevoflurane anesthesia. They were subjected to a battery of successive hippocampus-dependent tests following surgery, including open field test (OF), novel object recognition (NOR), fear conditioning test (FC), and Morris water maze (MWM). The integrated behavioral Z-scoring was applied to assess the hippocampus-dependent memory after anesthesia/surgery, and the association between the integrated behavioral Z-scores and hippocampal pro-inflammatory cytokines was explored. Results: Mice after anesthesia/surgery were found to have impaired hippocampus-dependent memory in NOR, FC, and MWM, but with different degrees in these aspects as represented by P value and effect size. The integrated memory Z-scores based on principal parameters of the above three tests can reduced the variability and increase the comprehensiveness of behavioral results. However, we found no statistic associations between hippocampal pro-inflammatory cytokines and the integrated Z-scores, as the elevated cytokines quickly return to normal on postoperative day 3 and/or day 7. Conclusions: The integrated Z-score methodology could facilitate the interpretation of the anesthesia/surgery induced cognitive decline in mice, and robustly quantify the behavioral phenotyping of hippocampus-dependent memory.